Bioefficacy, persistent toxicity, and persistence of translocated residues of seed treatment insecticides in maize against fall armyworm, Spodoptera frugiperda(J. E. Smith, 1797). (April 2022) - Suganthi, A.; Krishnamoorthy, S.V.; Sathiah, N.; Rabindra, R.J.; Muthukrishnan, N.; Jeyarani, S.; Vasantha kumar, S.; Karthik, P.; Selvi, C.; Arul Kumar, G.; Srinivasan, T.; Harishankar, K.; et al.
Abstract: The fall armyworm, Spodoptera frugiperda (J. E. Smith, 1797) emerged as a major threat to several maize growing countries worldwide. To manage this pest outbreak, farmers rely heavily on insecticides. Seed treatment with insecticides in maize is often the most pragmatic fall armyworm (FAW) management tactic. The aim of this work was to determine the bioefficacy, persistent toxicity, and persistence of translocated residues of insecticide seed treatments in maize used for the management of FAW. Bioefficacy of several seed treatment insecticides (Thiamethoxam, fipronil, tetraniliprole, chlorantraniliprole, cyantraniliprole + thiamethoxam, tetraniliprole + fipronil) was evaluated via foliar damage rating after crop emergence using the Tamil Nadu Agricultural University damage scoring scale. Persistent toxicity was assessed through a laboratory bioassay using the first instar larvae that fed on seed-treated maize leaves. Persistence of translocated residues was studied using Liquid Chromatography-Mass Spectrometry/Mass Spectrometry technique. Chlorantraniliprole 625 FS @ 6 ml kg −1 seed provided the highest protection followed by cyantraniliprole + thiamethoxam 19.8 FS, tetraniliprole 480 FS, and tetraniliprole + fipronil 240 FS. An increase in damage rating was observed 10 and 12 days post crop emergence. at 10 and 12 days post crop emergence with treatments involving diamides, except for chlorantraniliprole. Thiamethoxam and fipronil seed treatments were ineffective in FAW larvae management. Chlorantraniliprole residues persisted for >26 days, and cyantraniliprole + thiamethoxam residues persisted for >16 days in maize seedlings. The field bioefficacy of diamide insecticides residues matched with their toxicity persistence in laboratory bioassays, revealing them as best fit seed treatments when compared with thiamethoxam and fipronil. Seed treatment in maize with these diamide insecticides will be useful up to 15 days post crop emergence in preventing FAW foliar damage. Highlights: Seed treatment with chlorantraniliprole 625 FS gave highest protection against FAW. Diamides had persistent toxicity until 12–15 days after crop emergence. Chlorantraniliprole residues had higher persistence for>26 days in maize. Cyantraniliprole + Thiamethoxam residues persisted for >16 days.